1991
DOI: 10.1159/000163635
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Heat Shock Response in Human Monocytes-Macrophages

Abstract: The heat shock response represents a general physiological cellular reprograming of gene expression secondary to exposure to multiple different stresses such as heat or oxygen free radicals. It is assumed that this response is turned on in order to protect cells, or to permit better recovery, from the detrimental effects of such stresses. During erythrophagocytosis, heat shock proteins and heme oxygenase synthesis are induced in human monocytes-macrophages. Whereas induction of heme oxygenase appears to be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Phagocytosis of bacteria or bacterial products is usually coupled with the generation of oxygen free radicals or reactive oxygen species (ROS) [49]. Generation of ROS is an effective defense against bacteria, while it is also detrimental for the host cell, which could result in protein denaturation or proteotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of bacteria or bacterial products is usually coupled with the generation of oxygen free radicals or reactive oxygen species (ROS) [49]. Generation of ROS is an effective defense against bacteria, while it is also detrimental for the host cell, which could result in protein denaturation or proteotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that metabolism of heavy metals is usually coupled with the generation of oxygen free radicals or reactive oxygen species (ROS) [41,42]. Generation of excessive ROS could result in lipid oxidation and protein denaturation [5].…”
Section: Rat Hsp90αmentioning
confidence: 99%
“…5B). ROS (Feuer et al, 2003;Saraste et al, 2003;Donati et al, 1991). ROS mtHSP75 (Jönsson and Schill, 2007), mtHSP75 (Gao et al, 2008).…”
Section: 재료 및 방법unclassified